Investigating the Historical Influence of Islam in Java Through Bojonegoro's Wayang Thengul Art - Abdul Khamid; Nanang Setiawan; Muhammad Miftakhul Huda (Institut Agama Islam Al-Fatimah Bojonegoro, 2024)
This study aims to preserve the local culture of Indonesian society and serves as an educational medium to introduce the history of Islamic development to future generations. Moreover, amidst various opinions regarding the prohibition of wayang, this research reaffirms that Wali Songo also used wayang as a medium to spread Islam in Indonesia. This qualitative study employs in-depth interviews with wayang figures, as well as continuous observation and analysis to obtain valid data. The results of the study reveal that Wayang Tengul, beyond merely serving as a medium for introducing and educating people about the history of Islamic development in Indonesia, also plays a crucial and multifaceted role in fostering, nurturing, and maintaining a sense of religious moderation and tolerance among the diverse population of Bojonegoro Regency. This art form not only preserves historical narratives but also acts as a dynamic tool in promoting social cohesion and understanding within the community. This study contributes to enhancing knowledge literacy about local culture and developing insights into religious moderation in Indonesia. Through a deeper understanding of Wayang Tengul, it is hoped that this culture can continue to be preserved and appreciated as an essential part of the nation's cultural and historical heritage